Determination of the dose rate around a HDR 192Ir brachytherapy source with the microDiamond and the microSilicon detector - Giulio Rossi; Thomas Failing; Mark Gainey; Michael Kollefrath; Frank Hensley; Klemens Zink; Dimos Baltas (Zeitschrift für Medizinische Physik, 2023)
Purpose: To employ the microDiamond and the microSilicon detector (mDD and mSD, both PTW-Freiburg, Germany) to determine the dose rate around a HDR 192Ir brachytherapy source (model mHDR-v2r, Elekta AB, Sweden).Methods: The detectors were calibrated with a 60Co beam at the PTW Calibration Laboratory. Measurements around the 192Ir source were performed inside a PTW MP3 water phantom. The detectors were placed at selected points of measurement at radial distances r, ranging from 0.5 to 10 cm, keeping the polar angle θ = 90°. Additional measurements were performed with the mSD at fixed distances r = 1, 3 and 5 cm, with θ varying from 0 to 150°, 0 to 166°, and 0 to 168°, respectively. The corresponding mDD readings were already available from a previous work (Rossi et al., 2020). The beam quality correction factor of both detectors, as well as a phantom effect correction factor to account for the difference between the experimental geometry and that assumed in the TG-43 formalism, were determined using the Monte Carlo (MC) toolkit EGSnrc. The beam quality correction factor was factorized into energy dependence and volume-averaging correction factors. Using the abovementioned MC-based factors, the dose rate to water at the different points of measurement in TG-43 conditions was obtained from the measured readings, and was compared to the dose rate calculated according to the TG-43 formalism.Results: The beam quality correction factor was considerably closer to unity for the mDD than for the mSD. The energy dependence of the mDD showed a very weak radial dependence, similar to the previous findings showing a weak angular dependence as well (Rossi et al., 2020). Conversely, the energy dependence of the mSD decreased significantly with increasing distances, and also showed a considerably more pronounced angular dependence, especially for the smallest angles. The volume-averaging showed a similar radial dependence for both detectors: the correction had a maximal impact at 0.5 cm and then approached unity for larger distances, as expected. Concerning the angular dependence, the correction for the mSD was also similar to the one previously determined for the mDD (Rossi et al., 2020): a maximal impact was observed at θ = 0°, with values tending to unity for larger angles. In general, the volume-averaging was less pronounced for the mSD due to the smaller sensitive volume radius. After the application of the MC-based factors, differences between mDD dose rate measurements and TG-43 dose rate calculations ranged from −2.6% to +4.3%, with an absolute average difference of 1.0%. For the mSD, the differences ranged from −3.1% to +5.2%, with an absolute average difference of 1.0%. For both detectors, all differences but one were within the combined uncertainty (k = 2). The differences of the mSD from the mDD ranged from −3.9% to +2.6%, with the vast majority of them being within the combined uncertainty (k = 2). For θ ≠ 0°, the mDD was able to provide sufficiently accurate results even without the application of the MC-based beam quality correction factor, with differences to the TG-43 dose rate calculations from −1.9% to +3.4%, always within the combined uncertainty (k = 2).Conclusion: The mDD and the mSD showed consistent results and appear to be well suitable for measuring the dose rate around HDR 192Ir brachytherapy sources. MC characterization of the detectors response is needed to determine the beam quality correction factor and to account for energy dependence and/or volume-averaging, especially for the mSD. Our findings support the employment of the mDD and mSD for source QA, TPS verification and TG-43 parameters determination.